Policies on Prevention and Repression Against Sexual Violence for Higher Education: The Challenges and Expectations - Rahmasari, Helda; Pradityo, Randy; Karinda, Risna; Sitepu, Sudirman; Widyawati, Anis (IJCLS (Indonesian Journal of Criminal Law Studies), 2023)
The Government's Policies on Prevention and Repression against Sexual Voilance in Higher Education through the Regulation of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 30 of 2021 is a symbol of follow-up from the government to address the phenomenon of sexual violence in tertiary institutions in Indonesia. This study aims to analyze the challenges and expectations related to this policy. There are a number of qualitative and quantitative methods that are used in this study, which include interviews, questionnaires, and document analyses, and all are empirical research methods. There are several tertiary institutions in Indonesia, particularly those in Bengkulu City that have implemented Government's Policies on Prevention and Repression against Sexual Voilance in Higher Education, according to the results of this study. It is also important to note that there are also tertiary institutions that have not implemented these policies, but instead have their own policies or rules in regards to dealing with incidents of sexual violence at their institutions. A number of tertiary institutions, including tertiary schools in Indonesia, follow up on the rules governing the prevention and handling of sexual violence, but they follow policies that are not in line with the Regulation of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 30 of 2021 on Government's Policies on Prevention and Repression against Sexual Voilance in Higher Education.